1
$\begingroup$

Show that for $\forall x,y,z \in \mathbb{R},x^2+y^2+z^2\geq xy+yz+xz $.

I first assumed that $x\geq y \geq z$, but I'm having problems with the $z^2$. By itself, $z^2$ is clearly not greater than any of products of the other terms so I tried to show that $z^2+y^2$ was greater than something but failed. Can someone explain how I could prove this?

$\endgroup$
3
$\begingroup$

We have $(x-y)^2+(y-z)^2+(z-x)^2\ge0$. Expand, and we will get our inequality. And as a bonus we get that there is equality if and only if $x=y=z$.

$\endgroup$
1
$\begingroup$

All we need is the trivial inequality $x^2 \geq 0 $ for all $x$. Notice

$$ 2(x^2 + y^2 + z^2 - xy - yz - zx) = x^2 + x^2 + y^2+y^2 + z^2 + z^2 - 2xy - 2yx - 2xz = (x-y)^2 + (y-z)^2 + (z-x)^2 \geq 0$$

Hence,

$$ 2(x^2 + y^2 + z^2 - xy - yz - zx) \geq 0 \implies x^2 + y^2 + z^2 - xy - yz - zx \geq 0 \implies x^2 + y^2 + z^2 \geq xy + yz +zx$$

Another way to solve this problem. Using Cauchy-trick,

$$ (ab+bc+ca)^2 \leq (a^2 + b^2 + c^2)(b^2 + c^2+a^2) = (a^2+b^2+c^2)^2 $$

Squaring, gives desired result.

$\endgroup$
1
$\begingroup$

$$ x^2 + y^2 + z^2 - yz - zx - xy = \frac{3}{4} (-x+y)^2 + \frac{1}{4} (-x-y + 2 z)^2 $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.